Osseointegration of dental implants in ridges with insufficient bones using different membranes for guided bone regeneration - Vikas Vaibhav; Abhishek Sinha; Deepika Bolisetty; Abhishek Verma; Kunal Kumar; Sanjeev Singh (Wolters Kluwer Medknow Publications, 2021)
Background: The use of membrane with the guided bone regeneration (GBR) has been a controversial aspect of the implant placement, which helps achieve the primary graft stabilization and inhibit early graft loss. Objectives: The present clinical trial was aimed to determine the results of GBR with nonresorbable (expanded polytetrafluoroethylene [e-PTFE]) and resorbable (collagen) membrane both clinically and radiographically for 2 years with dental implant placement. Materials and Methods: 16 subjects having 32 sites for implant placement in a split-mouth pattern were included in the study. The sites for implant was prepared and grafted with the autogenous graft procured from the mandibular ramus area followed by graft coverage with either e-PTFE or collagen membrane. Various radiographic and clinical parameters were assessed for 2 years at an interval of 6 months each. The collected data were recorded for each study subject for all the implant sites and were statistically analyzed. Results: The mean values for periodontal probing depth at 6 months, 12 months, 18 months, and 24 months were 2.25 ± 0.17, 2.67 ± 1.84, 2.64 ± 1.21, and 3.01 ± 0.52, respectively, for the e-PTFE group. For the collagen group, the probing depth mean values at 6 months, 12 months, 18 months, and 24 months were 2.30 ± 0.14, 2.59 ± 1.76, 2.62 ± 1.30, and 2.98 ± 0.81, respectively. The corresponding clinical and radiographic parameters at all time intervals were nonsignificant on the intergroup comparison. Conclusion: Dental implants placed with simultaneous GBR have an acceptable survival rate at the end of 2 years irrespective of the resorbable or non-resorbable membrane used.